The neutron's children nuclear engineers and the shaping of identity - Johnston, Sean, 1956- (Oxford : Oxford University Press, 2012)
This account tracks the Allied atomic energy experts who emerged from the Manhattan Project to explore optimistic but distinct paths in the USA, UK and Canada. Characterised successively as admired atomic scientists, mistrusted spies and heroic engineers, their identities were ultimately shaped by nuclear accidents.
Description based on online resource; title from PDF title page (viewed on Apr. 20, 2012).
Includes bibliographical references and index.
Keywords: Nuclear engineers -- United States; Nuclear engineers -- Great Britain; Nuclear engineers -- Canada; Nuclear engineering -- United States -- History; Nuclear engineering -- Great Britain -- History; Nuclear engineering -- Canada -- History